The absence of protein Y4yS affects negatively the abundance of T3SS Mesorhizobium loti secretin, RhcC2, in bacterial membranes - Mercante, Virginia; Duarte, Cecilia M.; Sánchez, Cintia M.; Zalguizuri, Andrés; Caetano-Anollés, Gustavo; Lepek, Viviana C. (Frontiers in Plant Science, 2015)
Mesorhizobium loti MAFF303099 has a functional type III secretion system (T3SS) that is involved in the determination of nodulation competitiveness on Lotus. The M. loti T3SS cluster contains gene y4yS (mlr8765) that codes for a protein of unknown function (Y4yS). A mutation in the y4yS gene favors the M. loti symbiotic competitive ability on Lotus tenuis cv. Esmeralda and affects negatively the secretion of proteins through T3SS. Here we localize Y4yS in the bacterial membrane using a translational reporter peptide fusion. In silico analysis indicated that this protein presents a tetratricopeptide repeat (TPR) domain, a signal peptide and a canonical lipobox LGCC in the N-terminal sequence. These features that are shared with proteins required for the formation of the secretin complex in type IV secretion systems and in the Tad system, together with its localization, suggest that the y4yS-encoded protein is required for the formation of the M. loti T3SS secretin (RhcC2) complex. Remarkably, analysis of RhcC2 in the wild-type and M. loti y4yS mutant strains indicated that the absence of Y4yS affects negatively the accumulation of normal levels of RhcC2 in the membrane.